Returning to work after maternity leave: Childcare and workplace flexibility - Nowak, Margaret; Naude, Marita; Thomas, Gail (Sage Publications Ltd., 2012)
This article explores how responsibilities for childcare are managed as part of family decisions made around the return to work following a period of maternity leave. We surveyed all women health professionals identified as on maternity leave on payroll records of the Health Department, Western Australia, and one private sector national provider of hospital services. Survey questions were designed following a review of the literature and prior empirical work. The design enabled us to collect both quantitative information and interpretive qualitative responses from participants. Over 50% of respondents expected to have childcare provided wholly by family members, while 15% anticipated the use of formal arrangements alone. The planned arrangements for care can best be understood within a framework of a ‘family budget’ of time to be allocated between market-based work and childcare. Attitudes to childcare are central to this ‘time economies’ framework. Respondents experienced dissonance between the stated organizational family-friendly policy of their workplaces and practices at the management level. Employer-centred flexibility often disrupted their child-care arrangements. We identify important employment policy issues for workplaces that would facilitate the optimal return to the workforce by professional women following maternity leave.